Tropical Estuarine Macrobenthic Communities Are Structured by Turnover Rather than Nestedness - Medeiros, Carlinda Raílly (2016)
Turnover (i.e., species substitution) and nestedness (i.e., subsets of species from more diverse locations), the two main mechanisms used to explain the beta diversity of biological communities, have different implications for biodiversity conservation. To better understand how these mechanisms contribute to beta diversity, we tested the following hypotheses: (i) greater dissimilarity in community composition occurs between estuarine zones than other hierarchical level studied; (ii) beta diversity in these communities develops by turnover in estuaries with a lower degree of anthropogenic impact, but by nestedness in estuaries with a greater degree of anthropogenic impact; and (iii) the structuring mechanism is independent of season. We studied two tropical estuaries (dry and wet seasons) that vary in terms of land-use of the drainage basins. Subtidal benthic macroinvertebrates were sampled along the estuarine gradient in each of the two estuaries. The additive partitioning approach to species diversity was used to determine the hierarchical scale with the greatest dissimilarity in community composition. General beta diversity was measured using the Sorensen dissimilarity index, partitioning the turnover and nestedness components. The greatest dissimilarity in the composition of the communities occurred between the zones along the estuarine gradient in both seasons (dry = 58.6%; wet = 46.3%). In the estuary with a lower degree of anthropogenic influence, benthic macroinvertebrate diversity was generated by turnover regardless of the season. In the estuary with a greater degree of anthropogenic impact, beta diversity was structured by turnover during the dry season and a combination of both mechanisms during the wet season. We conclude that turnover is the principal mechanism responsible for beta diversity in benthic macroinvertebrate communities in tropical estuaries.